Perceptions of success and the power and control over change in women's lives with implications for adult education - Dorothy Wiese (Adult Education Research Conference, 1993)
The purpose of this research was to examine perceptions of success and the power and control over change in women's lives based on interviews with professional women living in St. Petersburg, Russia.